Analysis of Hospital Management's Commitment to the Implementation of the Occupational Safety and Health Management System at Cileungsi Hospital - Bekti Darmastuti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Occupational health is an important health element to pay attention to to build safe conditions at work. From national data, there was an increase in the incidence of work accidents by 35.6%. This data is different from global data which shows a 25% increase in the number of work accidents. One of the influencing factors is the commitment of the management. Hospitals as specialized bodies have a more complex risk in work accidents. Therefore, research is needed that shows the commitment of management in the implementation of the occupational safety and health management system. Objective: This study aims to analyze the commitment of hospital management in the implementation of SMK3 at Cileungsi Hospital Methods: This study is a qualitative research with triagnomy data collection techniques that are combined with interviews, observations and documentation studies. The research sample is eleven people who are workers from Cileungsi Hospital from several professions. Results: The results of this study show that the implementation of SMK3 at Cileungsi Hospital has not been fully implemented, even though the commitment of the Hospital Management has been seen with clear and documented guidelines, work programs and reports. However, the implementation has not been maximized due to the lack of socialization about SMK3, uneven training and lack of regular evaluation. Conclusion: The commitment of good hospital management needs to be supported by the implementation of good SMK3 to reduce the number of work accidents.